Scale-up of networked HIV treatment in Nigeria: Creation of an integrated electronic medical records system. Issue 1 (January 2015) - Chaplin, Beth; Meloni, Seema; Eisen, Geoffrey; Jolayemi, Toyin; Banigbe, Bolanle; Adeola, Juliette; Wen, Craig; Reyes Nieva, Harry; Chang, Charlotte; Okonkwo, Prosper; Kanki, Phyllis
Highlights An EMRS needs to be adapted to local infrastructure constraints and culture. Sharing information with HIV-positive patients has an effect on adherence. Implementation of a sustainable EMRS is an iterative process. It's important to plan for outcome data and to expect ongoing revision of the EMRS.